The Influence of Traditional Chinese Dance Forms on Contemporary Choreography (International Journal of Fine, Performing and Visual Arts, ISSN: 3006-6581, 2021)
This research delves into the dynamic intersection of visual arts and cultural diplomacy, with a particular focus on the unique context of Hong Kong. The study aims to investigate how visual arts serve as a powerful tool for fostering international relations, promoting cultural understanding, and shaping global perceptions of a region. Hong Kong, known for its rich cultural tapestry and global significance, provides an intriguing backdrop for examining the multifaceted role of visual arts in the realm of cultural diplomacy.